Let { x k } k = 1 n be a sequence whose terms come from { 2 , 3 , 6 } . If x 1 + x 2 + ⋯ + x n = 6 3 3 and x 1 2 1 + x 2 2 1 + ⋯ + x n 2 1 = 3 6 2 0 1 7 , find the value of n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Suppose the sequence contains a copies of 2 , b copies of 3 and c copies of 6 . Then we want to solve 2 a + 3 b + 6 c = 6 3 3 9 a + 4 b + c = 2 0 1 7 for nonnegative integers a , b , c . Eliminating b from these equations gives 1 9 a − 2 1 c 1 9 ( a − 3 5 1 9 0 ) = 3 5 1 9 = 3 5 1 9 ( 1 0 × 1 9 − 9 × 2 1 ) = 2 1 ( c − 3 1 6 7 1 ) and hence a = 3 5 1 9 0 − 2 1 u , c = 3 1 6 7 1 − 1 9 u for some integer u . This tells us that b = 5 2 u − 8 6 5 9 1 . Since a , b , c all need to be nonnegative, we deduce that u ≤ 1 6 7 5 , u ≥ 1 6 6 6 and u ≤ 1 6 6 6 respectively, and hence u = 1 6 6 6 .
Thus a = 2 0 4 , b = 4 1 and c = 1 7 , so that n = a + b + c = 2 6 2 .